The Role of Connexin 43 and Pannexin 1 During Acute Inflammation - Kameritsch, Petra; Pogoda, Kristin (Frontiers in Physiology, 2020)
During acute inflammation, the recruitment of leukocytes from the blood stream into the inflamed tissue is a well-described mechanism encompassing the interaction of endothelial cells with leukocytes allowing leukocytes to reach the site of tissue injury or infection where they can fulfill their function such as phagocytosis. This process requires a fine-tuned regulation of a plethora of signaling cascades, which are still incompletely understood. Here, connexin 43 (Cx43) and pannexin 1 (Panx1) are known to be pivotal for the correct communication of endothelial cells with leukocytes. Pharmacological as well as genetic approaches provide evidence that endothelial Cx43-hemichannels and Panx1-channels release signaling molecules including ATP and thereby regulate vessel function and permeability as well as the recruitment of leukocytes during acute inflammation. Furthermore, Cx43 hemichannels and Panx1-channels in leukocytes release signaling molecules and can mediate the activation and function of leukocytes in an autocrine manner. The focus of the present review is to summarize the current knowledge of the role of Cx43 and Panx1 in endothelial cells and leukocytes in the vasculature during acute inflammation and to discuss relevant molecular mechanisms regulating Cx43 and Panx1 function.